Cellulose‐Based Solid Fluorescent Materials. Issue 12 (16th August 2016) - Tian, Weiguo; Zhang, Jinming; Yu, Jian; Wu, Jin; Nawaz, Haq; Zhang, Jun; He, Jiasong; Wang, Fosong
Abstract : Organic solid‐state fluorescent materials have exhibited great potential application in optoelectronics, imaging, sensing, and security printing. However, the conventional conjugated luminogens such as perylene and pyrene derivatives are not highly recommended for preparation of the solid fluorescent materials because they always undergo fluorescence self‐quenching in solid state, i.e., aggregation caused quenching (ACQ) phenomenon. Herein, a series of solid materials with excellent fluorescent emission have been realized via covalently bonding the ACQ luminogens onto the cellulose chains and subsequently ionizing process. The synergy between the anchoring and diluting effect on luminogens of cellulose skeleton and the electrostatic repulsion among the ACQ luminogens efficiently inhibits the aggregation and the self‐quenching of luminogens. Such a general strategy is suitable for different ACQ luminogens and various partially substituted cellulose derivatives. Furthermore, the prepared fluorescent solids preserve the excellent properties of original cellulose derivatives such as good solubility and processibility. Therefore, they can be readily processed into materials in different forms, including printing pattern, coating, film, fiber, colloid, etc. This simple and effective strategy gives added impetus to the applications of solid fluorescent materials in practice. Abstract : A simple, effective, and general strategy is developed to fabricate solid‐state fluorescent materials from luminogens with aggregation‐caused quenching (ACQ). Furthermore, the abundance in raw materials (both cellulose and ACQ luminogens) gives added impetus to the applications in practice.